Pemanfaatan Tanah Mediteranian Sebagai Media Pembibitan Budset Tebu (Saccharum officinarum L.) Varietas Bululawang dengan Penambahan Pupuk Kandang pada Dosis yang Berbeda - Saktiyono Sigit Tri Pamungkas (Universitas Wahid Hasyim, 2021)
Abstract The decrease in the productivity of sugarcane (Saccharum officinarum L.) can be pursued through intensification with treatment in the nursery. However, it is increasingly difficult to find a good growing medium for plants, such as mediterranean soil must be managed. One of the efforts is to increase soil fertility by adding livestock manure which has the potential as organic fertilizer so that it is expected to improve soil structure and add nutrients. This study aims to determine the dose of organic fertilizer in sugarcane bud set nurseries on media with the addition of lime soil. This research was carried out at the independent farm. This study used a non-factorial Randomized Block Design (RAK) with one factor, namely the dose of organic fertilizer (0, 125, 250, 375, and 500 grams/polybag) with 3 replications. The results showed that the addition of organic fertilizer had a significant effect on plant height, number of leaves, and stem diameter of sugarcane nurseries. The best application of organic fertilizer in sugarcane bud set nurseries is a dose of 250 grams/polybag. Keywords: Sugarcane, Nurseries, Mediterranean Soil, Livestock Manure, Organic Fertilizer